PTU-315 Coeliac – supported, self help and management programme (c-sshamp); uk's first remote web-based management system for stable coeliac patients. (22nd June 2015) - Johnson, MW; Rostami, K; Marsh, M; Ciclitira, P
Abstract : Introduction: The 1:150 prevalence of coeliac patients in UK carries an economic burden and has created a dilemma for the NHS in how best to deal with the increasing numbers. The 2010 BSG guidelines on the "Management of coeliac disease in UK", 1 advocates that all coeliac patients should receive longterm review with someone experienced in coeliac management. Many Clinical Commissioning Groups have therefore recommended discharging these patients for community review. Unfortunately, we often find that these patients have not received the appropriate care and support they need, and are being re-referred back to the hospital once potentially avoidable long-term complications have already occurred. We set out to try and prevent this by developing a alternative, cost efficient, safe and effective method of managing our stable coeliac patients. Method: A 7 year retrospective analysis of all serology, duodenal histology and dietetic referrals requested through the Luton and Dunstable University Hospital was used to create a database of all local coeliac patients. With the support of Coeliac UK and our own local Coeliac Forum Group, we have developed personalised web-sites, using Patient Knows Best (PKB), to assist with the remote management of community based coeliac patients, whilst still providing hospital based specialist over-view. Results: We now have a database of 1264 coeliac patients. Since January 2014 we have steadily started moving our more stable patients on to our Coeliac – Supported, Self Help And Management Programme (C-SSHAMP). Presently this offers a personalised websites with a novel coeliac symptomatic monitoring system, an alert system if a patient score badly, a library of self help advice sheets and a record of their virtual consultations. The system provides a direct portal of access between patients and their specialists, can be converted into 14 different languages and has both iPhone or Android apps developed. Annually blood tests are reviewed through a virtual (telephone) clinic to monitor and support patients. Conclusion: C-SSHAMP is the first remote web-based management system in UK for stable coeliac disease patients. We believe we can automate much of the BSG guidance about annual review, whilst providing a "remote" presence which will act as a gentle reminder to improve compliance with acceptance and adjustment to a strict gluten free diet. By empowering our patients with the confidence and knowledge to monitor and manage their condition more effectively themselves, we aim to reduce the long term complication rate. Disclosure of interest: None Declared. Reference: Ciclitira P, Dewar DH, McLaughlin SD, et al . The management of adults with COELIAC disease. Br Soc Gastroenterol 2010